Highly corrosion-resistant negative-enthalpy high-manganese stainless steel material and method for manufacturing the same

CN122979770APending Publication Date: 2026-10-27SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611487083.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]基于上述现有技术的不足,本发明的目的在于提供一种高耐蚀的负焓高锰不锈钢材料及其制备方法,旨在解决现有高锰钢耐蚀性差的问题

Benefits of technology

[0039](1)本发明提供了一种FeaMnbAlcCrdMoeSifCg系列高耐蚀的负焓高锰不锈钢材料,通过调节不同密度金属元素的比例并加入超轻金属元素Al以调控合金的密度,同时,Si、C和Al元素与基体元素Fe、Mn具有负混合焓,负焓合金化能够限制基体/介质界面之间的原子扩散,从而提高耐蚀性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979770A_ABST
    Figure CN122979770A_ABST
Patent Text Reader

Abstract

The application discloses a high-corrosion-resistance negative-enthalpy high-manganese stainless steel material and a preparation method thereof. a Mn b Al c Cr d Mo e Si f C g ; wherein a, b, c, d, e, f and g respectively correspond to molar percentage distribution ratios of the elements, 10%≤b≤20%, 10%≤c≤15%, 2%≤d≤12%, 0 The application introduces the Cr element to promote the formation of a dense and stable chromium-rich oxide film on the surface of the steel, effectively preventing further corrosion of oxygen and corrosive media; on this basis, the Mo element is introduced to significantly promote the enrichment of chromium in the passivation film, further strengthen the passivation film, and help to improve the corrosion resistance; the provided negative-enthalpy high-manganese stainless steel material has a corrosion resistance reaching the grade of commercial 304 stainless steel, has low density and high corrosion resistance, and is widely applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal materials technology, and relates to a high corrosion-resistant negative enthalpy high manganese stainless steel material and its preparation method. Background Technology

[0002] High manganese steel is considered to have promising applications in fields such as rail transportation, mining machinery, marine vessels, and military equipment due to its excellent work hardening ability, impact resistance, wear resistance, and cost advantages.

[0003] However, the poor corrosion resistance of high-manganese steel is becoming increasingly prominent: manganese is highly chemically reactive in corrosive media, easily forming loose and unstable oxidation products, accelerating electrochemical corrosion reactions, and resulting in poor corrosion resistance of high-manganese steel itself (corrosion potential between -0.7 V and -0.3 V). With increasingly harsh service environments, railway frogs, marine equipment, and other components face complex corrosion from rainwater, salt spray, and acid mist. Existing corrosion resistance is no longer sufficient for long-term service requirements, and its performance directly determines the safety and service life of components. Simultaneously, existing material modification processes have significant potential for accelerating corrosion; for example, the potential difference between the second phase and the matrix can induce microgalvanic corrosion. Furthermore, the industry has not yet conducted systematic research on the corrosion mechanism, making it difficult for existing high-manganese steel to meet the long-term service requirements under extremely corrosive conditions.

[0004] Therefore, developing high-manganese stainless steel with high corrosion resistance is an urgent need to solve the industry's corrosion problem.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a high corrosion-resistant negative enthalpy high manganese stainless steel material and its preparation method, aiming to solve the problem of poor corrosion resistance of existing high manganese steel.

[0007] The present invention adopts the following technical solution:

[0008] A highly corrosion-resistant negative enthalpy high-manganese stainless steel material, wherein the negative enthalpy high-manganese stainless steel material is Fe a Mn b Al c Cr d Mo e Si f C g ,in:

[0009] a, b, c, d, e, f, and g correspond to the molar percentages of each element, with 10% ≤ b ≤ 20%, 10% ≤ c ≤ 15%, 2% ≤ d ≤ 12%, 0 < e ≤ 2%, 0 < f ≤ 5%, and 2% ≤ g ≤ 5%, with the balance being Fe and unavoidable impurities.

[0010] In a preferred embodiment of the present invention, the negative enthalpy high-manganese stainless steel material is composed of the following components in molar percentage:

[0011] Mn 12%-20%, Al 10%-15%, Cr 2%-12%, Mo 0%-2%, Si 2%-5% and C 3%-5%, with the balance being Fe and unavoidable impurities.

[0012] In the above technical solution, the purity of the iron, manganese, aluminum, chromium, molybdenum, silicon and carbon elements in the negative enthalpy high manganese stainless steel material is ≥99.8%.

[0013] Specifically, in the above technical solution, in the negative enthalpy high-manganese stainless steel material, iron and manganese elements have negative mixing enthalpies with aluminum, silicon, and carbon elements, respectively, wherein:

[0014] ΔH mix (Fe-Al) = -11 kJ / mol, ΔH mix (Fe-Si) = -35 kJ / mol, ΔH mix (Fe-C) = -50kJ / mol, ΔH mix (Mn-Al) = -19 kJ / mol, ΔH mix (Mn-Si) = -45 kJ / mol, ΔH mix (Mn-C) = -66kJ / mol.

[0015] Specifically, in the above technical solution, the mixed enthalpy of molybdenum with that of iron and chromium in the negative enthalpy high-manganese stainless steel material are as follows:

[0016] ΔHmix(Fe-Mo) = -2 kJ / mol, ΔHmix(Cr-Mo) = 0 kJ / mol.

[0017] In detail, in the above technical solution, the addition of Cr element is because chromium can promote the formation of a dense and stable chromium-rich oxide film (mainly composed of Cr2O3) on the surface of steel. This chromium-rich oxide film can effectively prevent further erosion by oxygen and corrosive media. Furthermore, the addition of Mo element can strengthen the passivation film because molybdenum can significantly promote the enrichment of chromium in the passivation film, making this protective film more stable.

[0018] More importantly, the enthalpy of mixing between Mo and Fe is negative (ΔH). mix (Fe-Mo) = -2 kJ / mol), inhibiting the rapid dissolution of Fe, thereby suppressing the formation of metastable pits; at the same time, the mixing enthalpy of Mo and Cr is 0 (ΔH). mix(Cr-Mo) = 0 kJ / mol) can effectively promote the diffusion of Cr and the repair of passivation film. Therefore, adding Mo helps to improve corrosion resistance.

[0019] Specifically, in the above technical solution, the negative enthalpy high-manganese stainless steel material is Fe. 64 Mn 13 Al 13 Cr2Mo 1.5 Si 2.5 C4, Fe 50 Mn 20 Al 10 Cr 12 Mo1Si5C2, Fe 65 Mn 10 Al 10 Cr6Mo 1.5 Si 3.5 C4, Fe 59 Mn 15 Al 14 Cr 5.5 Mo 0.5 Si1C5 and Fe 56 Mn 18 Al 11 One of Cr8Mo1Si2C4.

[0020] In another aspect, the present invention also provides a method for preparing the above-mentioned high corrosion-resistant negative enthalpy high manganese stainless steel material.

[0021] The negative enthalpy high-manganese stainless steel material is Fe a Mn b Al c Cr d Mo e Si f C g ;

[0022] in:

[0023] a, b, c, d, e, f, and g correspond to the molar percentages of each element, with 10% ≤ b ≤ 20%, 10% ≤ c ≤ 15%, 2% ≤ d ≤ 12%, 0 < e ≤ 2%, 0 < f ≤ 5%, and 2% ≤ g ≤ 5%, with the balance being Fe and unavoidable impurities.

[0024] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0025] According to the composition and molar percentage of the negative enthalpy high manganese stainless steel material, calculate and weigh each metal raw material, and put each metal raw material into a water-cooled metal crucible in order of melting point from low to high. The metal raw material with the lowest melting point is placed at the bottom, and the metal raw material with the highest melting point is placed on the surface. Sponge titanium is placed in the middle copper mold. Arc melting is carried out in an oxygen-free environment until it is fully mixed to obtain the negative enthalpy high manganese stainless steel material.

[0026] In the above technical solution, the oxygen-free environment is achieved through a process of vacuuming, argon filling, melting sponge titanium to absorb oxygen, and then vacuuming again.

[0027] Furthermore, in a preferred embodiment of the present invention, the process of vacuuming-argon filling-smelting sponge titanium with oxygen absorption-secondary vacuuming specifically comprises:

[0028] Use a mechanical pump to evacuate to a vacuum level of less than 5. Pa, then a molecular pump was used to evacuate to 4*10 Pa. -4 -7*10 -4 Pa, then 99.99% pure argon gas is introduced until the pressure reaches 0.04-0.05. MPa, followed by two arc-ignition melting processes of the sponge titanium (each arc-ignition melting process involves the sponge titanium being heated at high arc temperatures and visibly melting into a liquid state, during which oxygen is absorbed), absorbing residual oxygen, and finally using a mechanical pump to evacuate to a vacuum level of less than 5. Pa, and a molecular pump was used to evacuate the vacuum to 4*10 Pa. -4 -7*10 -4 Pa.

[0029] In the above technical solution, the number of times the metal raw material is ignited and melted is greater than 4. After each ignition and melting, the alloy in the crucible is turned over before the next ignition and melting is carried out.

[0030] In the above technical solution, the melting time for each arc ignition melting is 1.0-2.0 min, and in addition to the first and last arc ignition melting, the arc ignition melting of the metal raw material also includes magnetic stirring of the melt.

[0031] Furthermore, in the above technical solution, the melting time for each arc-ignition melting is 1.0-2.0 min, and in addition to the first and last arc-ignition melting, the arc-ignition melting of the metal raw material also includes magnetic stirring of the melt.

[0032] Specifically, in the above technical solution, the melting voltage and melting current of the arc-ignition melting are 10-15V and 200-300A, respectively.

[0033] In one specific embodiment of the present invention, the method for preparing the highly corrosion-resistant negative enthalpy high-manganese stainless steel material specifically includes the following steps:

[0034] S1. Place the various high-purity (purity greater than 99.9%) metal raw material particles (Fe, Mn, Al, Cr, Mo, Si and C) into an ultrasonic cleaner and clean them twice. Then, weigh and mix them according to the component ratio by mass percentage. Place them into a water-cooled metal crucible in order of melting point from low to high, with the element with the lowest melting point at the bottom and the element with the highest melting point at the top. At the same time, place sponge titanium at the middle copper mold position.

[0035] S2. Close the electric arc melting furnace door, turn on the circulating water, turn on the mechanical pump, and begin vacuuming. When the vacuum level is below 5 Pa, turn on the molecular pump to further evacuate the vacuum. When the vacuum level reaches 4*10 Pa... -4 -7.0*10 -4 At a pressure of 0.05 MPa, high-purity argon gas (99.99% purity, approximately 0.05 MPa) is introduced as a protective gas. Arc ignition is performed under this high-purity argon atmosphere, and the sponge titanium is melted twice to absorb residual oxygen in the furnace. Finally, the mechanical pump is turned on to create a vacuum. When the vacuum level drops below 5 Pa, the molecular pump is turned on for further vacuuming. When the vacuum level reaches 4*10 Pa... -4 -7.0*10 -4 Pa;

[0036] S3. First, high-current melting (melting voltage 10-15V, melting current 250-300 A) is used to melt and mix all metal particles evenly. After the alloy button is cast and cooled, it is flipped over by a robotic arm, and magnetic stirring is turned on. The second, third, and fourth arc-ignition meltings are performed sequentially using a lower melting current (melting voltage 10-15V, melting current 200-250 A) and the same melting time as the first arc-ignition melting. After each melting, the alloy button is flipped 180 degrees, the magnetic stirring is turned off, and the fifth arc-ignition melting is performed (melting voltage 10-15V, melting current 250-300 A, melting time 2 min) to make it into a smooth ingot, and then suction casting is performed (in order to fully melt the metal solution).

[0037] S4. After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0038] Compared with the prior art, the beneficial effects of the present invention are:

[0039] (1) This invention provides a Fe a Mn b Al c Cr d Mo eSi f C g This series of highly corrosion-resistant negative enthalpy high manganese stainless steel materials utilizes the proportions of metal elements with different densities and the addition of ultralight metal element Al to regulate the density of the alloy. Simultaneously, Si, C, and Al elements have negative mixing enthalpy with the matrix elements Fe and Mn. Negative enthalpy alloying can limit atomic diffusion between the matrix / medium interface, thereby improving corrosion resistance.

[0040] (2) The Fe provided by the present invention a Mn b Al c Cr d Mo e Si f C g The series of negative enthalpy high manganese stainless steel materials introduce Cr element to promote the formation of a dense and stable chromium-rich oxide film (mainly composed of Cr2O3) on the surface of the steel, which effectively prevents further corrosion by oxygen and corrosive media. On this basis, the introduction of Mo element significantly promotes the enrichment of chromium in the passivation film, thereby further strengthening the passivation film and helping to improve corrosion resistance.

[0041] (3) The Fe provided by the present invention a Mn b Al c Cr d Mo e Si f C g This series of negative enthalpy high-manganese stainless steel materials combines low density with high corrosion resistance, with a density of 6.5-6.7 g / cm³. 3 The corrosion potential is between -0.28 V and -0.2 V, and the pitting potential is between -0.09 V and -0.02 V, achieving corrosion resistance comparable to commercial 304 stainless steel. Attached Figure Description

[0042] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0043] Figure 1 The Fe prepared in Examples 1-5 of this invention a Mn b Al c Cr d Mo e Si f C gRoom temperature potentiodynamic polarization curves of 3.5 wt.% NaCl in a series of highly corrosion-resistant negative enthalpy high manganese stainless steel materials;

[0044] Figure 2 The room temperature potentiodynamic polarization curves of 3.5 wt.% NaCl for the negative enthalpy high manganese steel materials prepared in Comparative Examples 1-2 of this invention;

[0045] Figure 3 The Fe prepared in Example 5 of this invention 56 Mn 18 Al 11 Transmission electron microscope image of a cross section of Cr8Mo1Si2C4 negative enthalpy high manganese stainless steel.

[0046] Figure 4 The Fe prepared in Comparative Example 1 of this invention 56 Mn 15 Al 13 Transmission electron microscope image of a cross section of Cr8Si4C4 negative enthalpy high manganese steel;

[0047] Figure 5 The Fe prepared in Example 5 of this invention 56 Mn 18 Al 11 Comparison of surface photos of Cr8Mo1Si2C4 negative enthalpy high manganese stainless steel before and after 5 days of salt spray test.

[0048] Figure 6 The Fe prepared in Comparative Example 1 of this invention 56 Mn 15 Al 13 Comparison of surface photos of Cr8Si4C4 negative enthalpy high manganese steel before and after 5 days of salt spray test. Detailed Implementation

[0049] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments.

[0050] It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0051] In the embodiments, unless otherwise specified, all methods used are conventional methods in the art.

[0052] The terms “comprising,” “including,” or any other variations thereof, as used herein, are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.

[0053] Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0054] Traditional industries such as automobiles and coal mining highly value the improvement of steel's corrosion resistance. The development of high-corrosion-resistant steel aligns with market trends and is currently an urgent need in the steel industry. Developing low-density, high-manganese steel materials with excellent corrosion resistance can not only solve the shortage of high-performance metal materials required for major national projects such as automobiles, national defense weaponry, and deep-sea engineering, but also promote its practical application in key corrosion-resistant structural components in coal, chemical, industrial production, and national defense, playing a significant role in building a modern industrial system. However, current high-manganese steels typically exhibit low corrosion potentials (E0). corr It has a voltage of < -0.6 V and lacks resistance to pitting corrosion, exhibiting significant defects in corrosion resistance.

[0055] Based on this, embodiments of the present invention provide a low-density high-manganese steel material with pitting corrosion resistance, specifically a high-corrosion-resistant negative-enthalpy high-manganese stainless steel material, wherein the high-corrosion-resistant negative-enthalpy high-manganese stainless steel material comprises the following components in molar percentage:

[0056] Mn (manganese): 10%-20%, Al (aluminum): 10%-15%, Cr (chromium): 2%-12%, Mo (molybdenum): 0%-2%, Si (silicon): 0%-5%, C (carbon): 2%-5%, balance Fe and unavoidable impurities;

[0057] The molar percentages of Mo (molybdenum) and Si (silicon) are not set to 0.

[0058] In this embodiment of the invention, the high corrosion-resistant negative enthalpy high manganese stainless steel material may be free of impurities or may contain unavoidable impurities, but the number of moles of impurities is not included in the calculation of the mole percentage of the above components, that is, the sum of the mole percentages of the above components is 100%.

[0059] In this embodiment of the invention, the density of the alloy can be controlled by adjusting the proportion of metal elements with different densities and adding the ultralight metal element Al. At the same time, Si, C, and Al elements have negative mixing enthalpy characteristics with the matrix elements Fe and Mn. Relying on the negative enthalpy alloying mechanism, the corrosion resistance of the steel can be significantly improved.

[0060] Specifically, compared to traditional high-manganese steel, the embodiments of this invention add Al alloying element, as well as high content of Si and C elements. This is because Fe and Mn elements have a relatively negative mixing enthalpy ΔH with Al, Si, and C elements. mix Where: ΔH mix(Fe-Al) = -11 kJ / mol, ΔH mix (Fe-Si) = -35 kJ / mol, ΔH mix (Fe-C) = -50 kJ / mol, ΔH mix (Mn-Al) = -19 kJ / mol, ΔH mix (Mn-Si) = -45 kJ / mol, ΔH mix (Mn-C) = -66 kJ / mol. Furthermore, the enthalpy of mixing of molybdenum with iron and chromium are respectively: ΔH mix (Fe-Mo) = -2 kJ / mol, ΔH mix (Cr-Mo) = 0 kJ / mol.

[0061] Therefore, by adding negative enthalpy elements (Al, Si, C), differences in chemical affinity between elements can be generated, thereby forming localized negative enthalpy chemical affinity clusters (heterogeneous structures) in the austenitic structure, such as compositional fluctuations and localized order. These nano-heterogeneous interfaces can construct locally strong chemical interaction systems within the alloy, effectively improving the interface structure and chemical stability of the alloy. The locally strong chemical interactions formed by the introduction of negative enthalpy elements can effectively inhibit the electrochemical corrosion reaction of the metal matrix, significantly delay the dissolution rate of the metal material in the corrosive environment, improve the corrosion resistance of the alloy from the microstructural level, and ultimately achieve a significant improvement in the corrosion resistance of high-manganese steel alloys. At the same time, the addition of ultra-light Al elements can optimize the overall density of the alloy, achieving lightweight control of the alloy without sacrificing corrosion resistance. The negative enthalpy high-manganese stainless steel material provided in this embodiment of the invention has significantly improved corrosion resistance, with a mixed enthalpy value between -16.4 and -14.7 kJ / mol and a density of 6.5-6.7 g / cm³. 3 With corrosion potentials between -0.28V and -0.2V, and pitting potentials between -0.09V and -0.02V, it has great application potential in major fields such as transportation, aerospace, marine vessels, and national defense.

[0062] In other words, the high corrosion-resistant negative enthalpy high manganese stainless steel material provided in the embodiments of the present invention can be denoted as Fe. a Mn b Al c Cr d Mo e Si f C g Where: a, b, c, d, e, f and g correspond to the molar ratios of each element, 10%≤b≤20%, 10%≤c≤15%, 2%≤d≤12%, 0<e≤2%, 0<f≤5%, 2%≤g≤5%.

[0063] In some embodiments, the highly corrosion-resistant negative enthalpy high-manganese stainless steel material comprises the following components in molar percentage:

[0064] Mn 12%-20%, Al 10%-15%, Cr 2%-12%, Mo 0%-2%, Si 2%-5% and C 3%-5% (Mo and Si contents are not taken as 0), with the balance being Fe and unavoidable impurities.

[0065] In this embodiment, the negative enthalpy high-manganese stainless steel material possesses both low density and corrosion resistance, with a density of 6.5-6.7 g / cm³. 3 The corrosion potential is between -0.28 V and -0.2 V, and the pitting potential is between -0.09 V and -0.02 V (it has excellent resistance to pitting corrosion).

[0066] A second aspect of the present invention provides a method for preparing a highly corrosion-resistant negative enthalpy high-manganese stainless steel material, comprising the following steps:

[0067] S1. Weigh each raw material according to the composition and molar percentage of the negative enthalpy high manganese stainless steel material, and put each raw material into the container in order of melting point from low to high, with the raw material with the lowest melting point at the bottom and the raw material with the highest melting point at the top.

[0068] S2. Arc melting is carried out in an oxygen-free environment to obtain the negative enthalpy high manganese stainless steel material.

[0069] The preparation method provided by this invention is simple and easy to operate, and the prepared negative enthalpy high manganese stainless steel material has both low density and corrosion resistance.

[0070] In step S1, the raw materials are placed into the container in order of increasing melting point, with the lowest melting point material at the bottom and the highest melting point material at the top. This allows the low-melting-point materials to melt first, forming a liquid molten pool as a heat conduction medium, which accelerates the melting rate of the high-melting-point materials and shortens the total melting time. At the same time, it can also avoid the high-melting-point materials from directly contacting the high-temperature electric arc, which would cause instantaneous thermal stress and thus reduce the risk of thermal fatigue cracks on the inner wall of the container.

[0071] In some embodiments, Fe raw materials, Mn raw materials, Al raw materials, Cr raw materials, Mo raw materials, Si raw materials and C raw materials are weighed according to the composition and molar percentage of the negative enthalpy high manganese stainless steel material, wherein the purity of Fe raw materials, Mn raw materials, Al raw materials, Cr raw materials, Mo raw materials, Si raw materials and C raw materials is greater than or equal to 99.8%.

[0072] In some embodiments, the container is a water-cooled metal crucible.

[0073] In step S2, in some embodiments, the current used for arc ignition melting is 200-300 A, for example, it can be 200 A, 210 A, 220 A, 230 A, 240 A, 250 A, 260 A, 270 A, 280 A, 290 A or 300 A, etc.

[0074] In some embodiments, the number of arc-ignition melting operations is greater than 4 (e.g., 5, 6, 7, or 8 times), and the time for each arc-ignition melting operation is independently 1-2 minutes (e.g., 1 minute, 1.1 minute, 1.2 minute, 1.3 minute, 1.4 minute, 1.5 minute, 1.6 minute, 1.7 minute, 1.8 minute, 1.9 minute, or 2 minutes). After each arc-ignition melting operation, the alloy in the container is flipped (i.e., rotated 180 degrees) before the next arc-ignition melting operation is performed. The flipping operation can force the melt to flow, promote diffusion homogenization, and help eliminate compositional segregation.

[0075] In some implementations, in addition to the initial and final arc-ignition melting, the melt is stirred (e.g., magnetically stirred) during the arc-ignition melting process. This allows the raw materials to be mixed more thoroughly and evenly, resulting in a more uniform alloy composition.

[0076] In some embodiments, the raw materials are placed into the container in order of increasing melting point, and sponge titanium is added during the process of adding the raw materials; the oxygen-free environment is achieved by a process of vacuuming, filling with argon gas, melting sponge titanium to absorb oxygen, and vacuuming again.

[0077] In some embodiments, the process of vacuuming, argon filling, oxygen absorption during sponge titanium melting, and vacuuming again specifically includes:

[0078] Vacuum up to 4×10 -4 -7×10 -4 Pa, then 99.99% pure argon gas is introduced to 0.04-0.05 MPa, and the sponge titanium is melted twice by arc ignition to absorb residual oxygen. Finally, a vacuum is drawn to 4×10 Pa. -4 -7×10 -4 Pa.

[0079] In some embodiments, the processes of vacuuming, argon filling, oxygen absorption during titanium sponge melting, and vacuuming specifically include:

[0080] A mechanical pump was used to evacuate the vacuum to a level less than 5 Pa, followed by a molecular pump to evacuate the vacuum to 4 × 10⁻⁶ Pa. -4 -7×10 -4Pa, then 99.99% pure argon gas is introduced to 0.04-0.05 MPa, and the sponge titanium is melted twice by arc ignition to absorb residual oxygen;

[0081] Then, a vacuum of 4 × 10⁻⁶ was created using mechanical and molecular pumps. -4 -7×10 -4 Pa (i.e., using a mechanical pump to evacuate to a vacuum level of less than 5 Pa, and then using a molecular pump to evacuate to 4 × 10 Pa). -4 -7×10 -4 Pa).

[0082] Further, after completing vacuuming, argon filling, oxygen absorption during sponge titanium melting, and vacuuming again, the arc melting of various raw materials (Fe, Mn, Al, Cr, Mo, Si, and C) is carried out.

[0083] The present invention will be further described below through specific embodiments.

[0084] Example 1

[0085] This embodiment provides a highly corrosion-resistant negative enthalpy high-manganese stainless steel material, which comprises the following components in molar percentage: Fe 64%, Mn 13%, Al 13%, Cr 2%, Mo 1.5%, Si 2.5%, and C 4%, which can be denoted as Fe 64 Mn 13 Al 13 Cr2Mo 1.5 Si 2.5 C4 has a mixing enthalpy of -15.5 kJ / mol.

[0086] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0087] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 1, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0088] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4At a pressure of 0.05 MPa, 99.99% pure argon gas (as a protective gas) is introduced, and sponge titanium is arc-melted twice under a high-purity argon atmosphere to absorb residual oxygen. Then, a vacuum is drawn up to 7 × 10⁻⁶ MPa using both mechanical and molecular pumps. -4 After Pa, the raw materials are then subjected to arc-ignition melting. The specific steps of arc-ignition melting are as follows:

[0089] The first arc ignition melting is carried out using a large current (melting current is 260 A, melting time is 2 min), which melts and mixes all raw material particles evenly. After the alloy button is cast and cooled, it is flipped over by a robot.

[0090] Turn on the magnetic stirrer, and use a smaller melting current (specifically 220 A) and the same melting time as the first arc ignition melting to perform the second, third and fourth arc ignition melting in sequence. After each melting, the alloy button casting needs to be rotated 180 degrees.

[0091] Turn off the magnetic stirring and perform the fifth arc ignition melting (melting current of 280 A, melting time of 2 min) to make it into a smooth ingot, and then perform suction casting to fully melt the metal solution;

[0092] After the alloy button ingot has completely cooled, open the furnace door and remove the sample.

[0093] Example 2

[0094] This embodiment provides a highly corrosion-resistant negative enthalpy high-manganese stainless steel material, which comprises the following components in molar percentage: Fe 50%, Mn 20%, Al 10%, Cr 12%, Mo 1%, Si 5%, and C 2%, which can be denoted as Fe 50 Mn 20 Al 10 Cr 12 Mo1Si5C2 has a mixing enthalpy of -14.7 kJ / mol.

[0095] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0096] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 2, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0097] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At a pressure of 0.05 MPa, 99.99% pure argon gas (as a protective gas) is introduced, and sponge titanium is arc-melted twice under a high-purity argon atmosphere to absorb residual oxygen. Then, a vacuum is drawn up to 7 × 10⁻⁶ MPa using both mechanical and molecular pumps. -4 After Pa, the raw materials are then subjected to arc-ignition melting. The specific steps of arc-ignition melting are as follows:

[0098] The first arc ignition melting is carried out using a large current (melting current is 260 A, melting time is 2 min), which melts and mixes all raw material particles evenly. After the alloy button is cast and cooled, it is rotated 180 degrees by a robot.

[0099] Turn on the magnetic stirrer, and use a smaller melting current (specifically 220 A) and the same melting time as the first arc ignition melting to perform the second, third and fourth arc ignition melting in sequence. After each melting, the alloy button casting needs to be rotated 180 degrees.

[0100] Turn off the magnetic stirring and perform the fifth arc ignition melting (melting current of 280 A, melting time of 2 min) to make it into a smooth ingot, and then perform suction casting to fully melt the metal solution;

[0101] After the alloy button ingot has completely cooled, open the furnace door and remove the sample.

[0102] Example 3

[0103] This embodiment provides a highly corrosion-resistant negative enthalpy high-manganese stainless steel material, which comprises the following components in molar percentage: Fe 65%, Mn 10%, Al 10%, Cr 6%, Mo 1.5%, Si 3.5%, and C 4%, which can be denoted as Fe 65 Mn 10 Al 10 Cr6Mo 1.5 Si 3.5 C4 has a mixing enthalpy of -15.8 kJ / mol.

[0104] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0105] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 3, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0106] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At a pressure of 0.05 MPa, 99.99% pure argon gas (as a protective gas) is introduced, and sponge titanium is arc-melted twice under a high-purity argon atmosphere to absorb residual oxygen. Then, a vacuum is drawn up to 7 × 10⁻⁶ MPa using both mechanical and molecular pumps. -4 After Pa, the raw materials are then subjected to arc-ignition melting. The specific steps of arc-ignition melting are as follows:

[0107] The first arc ignition melting is carried out using a large current (melting current is 260 A, melting time is 2 min), which melts and mixes all raw material particles evenly. After the alloy button is cast and cooled, it is flipped over by a robot.

[0108] Turn on the magnetic stirrer, and use a smaller melting current (specifically 220 A) and the same melting time as the first arc ignition melting to perform the second, third and fourth arc ignition melting in sequence. After each melting, the alloy button casting needs to be rotated 180 degrees.

[0109] Turn off the magnetic stirring and perform the fifth arc ignition melting (melting current of 280 A, melting time of 2 min) to make it into a smooth ingot, and then perform suction casting to fully melt the metal solution;

[0110] After the alloy button ingot has completely cooled, open the furnace door and remove the sample.

[0111] Example 4

[0112] This embodiment provides a highly corrosion-resistant negative enthalpy high-manganese stainless steel material, which comprises the following components in molar percentage: Fe 59%, Mn 15%, Al 14%, Cr 5.5%, Mo 0.5%, Si 1%, and C 5%, which can be denoted as Fe 59 Mn 15 Al 14 Cr 5.5 Mo 0.5Si1C5 has a mixing enthalpy of -16.4 kJ / mol.

[0113] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0114] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 4, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0115] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At a pressure of 0.05 MPa, 99.99% pure argon gas (as a protective gas) is introduced, and sponge titanium is arc-melted twice under a high-purity argon atmosphere to absorb residual oxygen. Then, a vacuum is drawn up to 7 × 10⁻⁶ MPa using both mechanical and molecular pumps. -4 After Pa, the raw materials are then subjected to arc-ignition melting. The specific steps of arc-ignition melting are as follows:

[0116] The first arc ignition melting is carried out using a large current (melting current is 260 A, melting time is 2 min), which melts and mixes all raw material particles evenly. After the alloy button is cast and cooled, it is flipped over by a robot.

[0117] Turn on the magnetic stirrer, and use a smaller melting current (specifically 220 A) and the same melting time as the first arc ignition melting to perform the second, third and fourth arc ignition melting in sequence. After each melting, the alloy button casting needs to be rotated 180 degrees.

[0118] Turn off the magnetic stirring and perform the fifth arc ignition melting (melting current of 280 A, melting time of 2 min) to make it into a smooth ingot, and then perform suction casting to fully melt the metal solution;

[0119] After the alloy button ingot has completely cooled, open the furnace door and remove the sample.

[0120] Example 5

[0121] This embodiment provides a highly corrosion-resistant negative enthalpy high-manganese stainless steel material, which comprises the following components in molar percentage: Fe 56%, Mn 18%, Al 11%, Cr 8%, Mo 1%, Si 2%, and C 4%, which can be denoted as Fe 56 Mn 18 Al 11 Cr8Mo1Si2C4 has a mixing enthalpy of -15.0 kJ / mol.

[0122] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0123] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 5, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0124] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At a pressure of 0.05 MPa, 99.99% pure argon gas (as a protective gas) is introduced, and sponge titanium is arc-melted twice under a high-purity argon atmosphere to absorb residual oxygen. Then, a vacuum is drawn up to 7 × 10⁻⁶ MPa using both mechanical and molecular pumps. -4 After Pa, the raw materials are then subjected to arc-ignition melting. The specific steps of arc-ignition melting are as follows:

[0125] The first arc ignition melting is carried out using a large current (melting current is 260 A, melting time is 2 min), which melts and mixes all raw material particles evenly. After the alloy button is cast and cooled, it is flipped over by a robot.

[0126] Turn on the magnetic stirrer, and use a smaller melting current (specifically 220 A) and the same melting time as the first arc ignition melting to perform the second, third and fourth arc ignition melting in sequence. After each melting, the alloy button casting needs to be rotated 180 degrees.

[0127] Turn off the magnetic stirring and perform the fifth arc ignition melting (melting current of 280 A, melting time of 2 min) to make it into a smooth ingot, and then perform suction casting to fully melt the metal solution;

[0128] After the alloy button ingot has completely cooled, open the furnace door and remove the sample.

[0129] Comparative Example 1

[0130] This comparative example provides a high corrosion-resistant negative enthalpy high manganese steel material, comprising the following molar percentage components: Fe 56%, Mn 15%, Al 13%, Cr 8%, Si 4%, and C 4%, which can be denoted as Fe 56 Mn 15 Al 13 Cr8Si4C4 has a mixing enthalpy of -18.08 kJ / mol.

[0131] The preparation method of the negative enthalpy high manganese steel material includes the following steps:

[0132] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Comparative Example 1, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0133] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0×10-4 Pa, introduce 99.99% pure argon gas (as a protective gas) to 0.05 MPa. Arc melt the sponge titanium twice in a high-purity argon atmosphere to absorb residual oxygen. Then, perform vacuuming again with the mechanical pump and molecular pump to 7×10-4 Pa before performing arc melting of the raw materials. The specific steps of arc melting are as follows:

[0134] The first arc ignition melting is carried out using a large current (melting current is 260 A, melting time is 2 min), which melts and mixes all raw material particles evenly. After the alloy button is cast and cooled, it is flipped over by a robot.

[0135] Turn on the magnetic stirrer, and use a smaller melting current (specifically 220 A) and the same melting time as the first arc ignition melting to perform the second, third and fourth arc ignition melting in sequence. After each melting, the alloy button casting needs to be rotated 180 degrees.

[0136] Turn off the magnetic stirring and perform the fifth arc ignition melting (melting current of 280 A, melting time of 2 min) to make it into a smooth ingot, and then perform suction casting to fully melt the metal solution;

[0137] After the alloy button ingot has completely cooled, open the furnace door and remove the sample.

[0138] Comparative Example 2

[0139] This comparative example provides a high corrosion-resistant negative enthalpy high manganese steel material, comprising the following molar percentage components: Fe 46%, Mn 30%, Al 13%, Cr 4%, Mo 1%, Si 2%, and C 4%, which can be denoted as Fe 46 Mn 30 Al 13 Cr4Mo1Si2C4 has a mixing enthalpy of -16.4 kJ / mol.

[0140] The preparation method of the negative enthalpy high manganese steel material includes the following steps:

[0141] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Comparative Example 2, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0142] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0×10-4 Pa, introduce 99.99% pure argon gas (as a protective gas) to 0.05 MPa. Arc melt the sponge titanium twice in a high-purity argon atmosphere to absorb residual oxygen. Then, perform vacuuming again with the mechanical pump and molecular pump to 7×10-4 Pa before performing arc melting of the raw materials. The specific steps of arc melting are as follows:

[0143] The first arc ignition melting is carried out using a large current (melting current is 260 A, melting time is 2 min), which melts and mixes all raw material particles evenly. After the alloy button is cast and cooled, it is flipped over by a robot.

[0144] Turn on the magnetic stirrer, and use a smaller melting current (specifically 220 A) and the same melting time as the first arc ignition melting to perform the second, third and fourth arc ignition melting in sequence. After each melting, the alloy button casting needs to be rotated 180 degrees.

[0145] Turn off the magnetic stirring and perform the fifth arc ignition melting (melting current of 280 A, melting time of 2 min) to make it into a smooth ingot, and then perform suction casting to fully melt the metal solution;

[0146] After the alloy button ingot has completely cooled, open the furnace door and remove the sample.

[0147] test:

[0148] Based on Archimedes' principle, the Fe prepared in Examples 1-5 was measured respectively. a Mn b Al c Cr d Mo e Si f C g The masses of the series of high corrosion-resistant negative enthalpy high manganese stainless steel materials and the negative enthalpy high manganese steel materials prepared in Comparative Examples 1-2 were measured in air and immersed in the test fluid. Substituting these masses into the corresponding formulas, the densities of each sample were calculated. The results show that the high corrosion-resistant negative enthalpy high manganese stainless steel material provided by this invention has a low density. Among these, Fe... 64 Mn 13 Al 13 Cr2Mo 1.5 Si 2.5 The density of C4 is 6.6 g / cm³. 3 Fe 50 Mn 20 Al 10 Cr 12 The density of Mo1Si5C2 is 6.5 g / cm³. 3 Fe 65 Mn 10 Al 10 Cr6Mo 1.5 Si 3.5 The density of C4 is 6.7 g / cm³. 3 Fe 59 Mn 15 Al 14 Cr 5.5 Mo 0.5 The density of Si1C5 is 6.5 g / cm³. 3 Fe 56 Mn 18 Al 11 The density of Cr8Mo1Si2C4 is 6.7 g / cm³. 3 .

[0149] Corrosion resistance test: Using a CS 235M potentiostat, the Fe prepared in Examples 1-5 were tested respectively. a Mn b Al c Cr d Mo e Si f C gThe pitting corrosion resistance of a series of highly corrosion-resistant negative enthalpy high-manganese stainless steel materials and negative enthalpy high-manganese steel materials prepared in Comparative Examples 1-2 was investigated in a 3.5 wt.% NaCl aqueous solution (25±1 ℃). Specifically, a three-electrode electrolytic cell was used: a saturated calomel reference electrode, a platinum sheet counter electrode, and a working electrode for the high-manganese steel material sample. The working electrode sample size was 12.5×8×1 mm. 3 After the copper wire is connected, it is sealed with epoxy resin by cold mounting; the potentiodynamic polarization test starts from -0.5V of the corrosion potential Ecorr and scans towards the anode at a rate of 0.167 mV / s until the pitting potential signal appears.

[0150] Figure 1 The Fe prepared in Examples 1-5 of this invention a Mn b Al c Cr d Mo e Si f C g Room temperature potentiodynamic polarization curves of 3.5 wt.% NaCl in a series of highly corrosion-resistant negative enthalpy high manganese stainless steel materials; Figure 2 The table shows the room temperature potentiodynamic polarization curves of the negative enthalpy high manganese steel materials prepared in Comparative Examples 1-2 of this invention with 3.5 wt.% NaCl.

[0151] from Figure 1-2 As can be seen from the table below, the high corrosion-resistant negative enthalpy high manganese stainless steel material prepared in the embodiments of the present invention has good corrosion resistance; the specific results are shown in Table 1 below.

[0152] Table 1. Corrosion potential and pitting potential of the materials prepared in Examples 1-5 and Comparative Examples 1-2

[0153] Example 1 <![CDATA[Fe 64 Mn 13 Al 13 Cr2Mo 1.5 Yes 2.5 C4]]> -0.25 -0.09 Example 2 <![CDATA[Fe 50 Mn 20 Al 10 Cr 12 Mo1Si5C2]]> -0.28 -0.02 Example 3 <![CDATA[Fe 65 Mn 10 Al 10 Cr6Mo 1.5 Yes 3.5 C4]]> -0.2 -0.04 Example 4 <![CDATA[Fe 59 Mn 15 Al 14 Cr 5.5 Mo 0.5 Si1C5]]> -0.26 -0.08 Example 5 <![CDATA[Fe 56 Mn 18 Eel 11 Cr8Mo1Si2C4]]> -0.24 -0.03 Comparative Example 1 <![CDATA[Fe 56 Mn 15 Al 13 Cr8Si4C4]]> -0.36 -0.28 Comparative Example 2 <![CDATA[Fe 46 Mn 30 Al 13 Cr4Mo1Si2C4]]> -0.45 / (No passivation behavior)

[0154] Figure 3 The Fe prepared in Example 5 of this invention 56 Mn 18 Al 11 Transmission electron microscope (TEM) image of a cross-section of Cr8Mo1Si2C4 negative enthalpy high-manganese stainless steel. Figure 4 The Fe prepared in Comparative Example 1 of this invention 56 Mn 15 Al 13 Transmission electron microscope (TEM) image of a cross-section of Cr8Si4C4 negative enthalpy high manganese steel. TEM samples were prepared using focused ion beam cutting (FIB), typically employing an "in-situ extraction-thinning" process, specifically including: (1) locating the sample surface region within the bulk sample and depositing a Pt protective layer on the surface to prevent subsequent ion beam damage and surface contamination; (2) using Ga… +The ion beam etches U-shaped grooves on both sides of the target area and then cuts off the bottom to form a thin film about a few micrometers thick; (3) a micro-manipulation probe (needle) is brought close to the thin film and Pt is deposited to weld the probe to the thin film. After cutting off the residual connection, it is lifted out; (4) the thin film is transferred to the semi-circular grid of the transmission electron microscope and fixed with Pt deposition; (5) the ion beam voltage and current are gradually reduced to thin the thin film to the electronically transparent thickness (thickness <100 nm). Finally, it is cleaned with a low-energy ion beam to remove the amorphous damage layer.

[0155] contrast Figure 3-4 It can be seen that the Fe prepared in Example 5 56 Mn 18 Al 11 Both the Cr8Mo1Si2C4 negative enthalpy high manganese stainless steel and the negative enthalpy high manganese steel prepared in Comparative Example 1 have an oxide film formed on their surfaces; furthermore, by comparison, it can be seen that... Figure 3 It can also be clearly seen that the introduction of Mo promotes the enrichment of chromium, thereby strengthening the formation of a passivation film at the interface. The passivation film is thicker and denser, which can effectively improve its corrosion resistance (making the pitting potential closer to 0).

[0156] According to national standard GB / T 10125-2021, the Fe prepared in Example 5 of this invention... 56 Mn 18 Al 11 Cr8Mo1Si2C4 negative enthalpy high manganese stainless steel material and Fe prepared in Comparative Example 1 56 Mn 15 Al 13 Cr8Si4C4 negative enthalpy high manganese steel material was subjected to salt spray test under the same conditions (this test accelerates the corrosion process by spraying salt-containing mist, and can evaluate the corrosion resistance of materials in marine or industrial atmospheric environments in a short time, and is widely used in machinery, electronics, automobile and defense industries).

[0157] Figure 5 and Figure 6 The Fe prepared in Example 5 of this invention are respectively 56 Mn 18 Al 11 Cr8Mo1Si2C4 negative enthalpy high manganese stainless steel material and Fe prepared in Comparative Example 1 56 Mn 15 Al 13 Comparison of surface photographs of Cr8Si4C4 negative enthalpy high manganese steel before and after 5 days of salt spray testing; Figure 5 and Figure 6 It can be seen that the Fe prepared in Example 5 of this invention 56 Mn 18Al 11 The corrosion resistance of Cr8Mo1Si2C4 negative enthalpy high manganese stainless steel (which showed no corrosion after salt spray testing and retained the metallic luster of its surface before the salt spray test) is significantly better than that of the Fe prepared in Comparative Example 1. 56 Mn 15 Al 13 Cr8Si4C4 negative enthalpy high manganese steel material (completely corroded after salt spray test).

[0158] In summary, this invention provides a novel high-corrosion-resistant negative enthalpy high-manganese stainless steel material and its preparation method. This invention can regulate the alloy density by adjusting the proportions of metal elements with different densities and adding the ultralight metal element Al. Simultaneously, Si, C, and Al elements have a negative mixing enthalpy with the matrix element Fe, and negative enthalpy alloying can significantly improve corrosion resistance. By introducing Cr element, a dense and stable chromium-rich oxide film (mainly composed of Cr2O3) is formed on the steel surface, effectively preventing further erosion by oxygen and corrosive media. Furthermore, the introduction of Mo element significantly promotes the enrichment of chromium in the passivation film, thereby further strengthening the passivation film and contributing to improved corrosion resistance.

[0159] Therefore, the high corrosion-resistant negative enthalpy high-manganese stainless steel material provided by this invention has good application prospects, combining low density and corrosion resistance synergistically, with a density of 6.5-6.7 g / cm³. 3 The corrosion potential is between -0.28 V and -0.2 V, and the pitting potential is between -0.09 V and -0.02 V.

[0160] The above embodiments are merely examples of several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention patent.

[0161] It should be noted that those skilled in the art can make various modifications and improvements without departing from the inventive concept, and these all fall within the scope of protection of this invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A highly corrosion-resistant negative enthalpy high-manganese stainless steel material, characterized in that, The negative enthalpy high-manganese stainless steel material is Fe a Mn b Al c Cr d Mo e Si f C g ; in: a, b, c, d, e, f, and g correspond to the molar percentages of each element, with 10% ≤ b ≤ 20%, 10% ≤ c ≤ 15%, 2% ≤ d ≤ 12%, 0 < e ≤ 2%, 0 < f ≤ 5%, and 2% ≤ g ≤ 5%, with the balance being Fe and unavoidable impurities.

2. The high corrosion-resistant negative enthalpy high manganese stainless steel material according to claim 1, characterized in that, The negative enthalpy high-manganese stainless steel material is composed of the following components in molar percentage: Mn 12%-20%, Al 10%-15%, Cr 2%-12%, Mo 0%-2%, Si 2%-5% and C 3%-5%, with the balance being Fe and unavoidable impurities.

3. The high corrosion-resistant negative enthalpy high manganese stainless steel material according to claim 1, characterized in that, In the negative enthalpy high manganese stainless steel material, the purity of the iron, manganese, aluminum, chromium, molybdenum, silicon and carbon elements in the corresponding raw materials is ≥99.8%.

4. The high corrosion-resistant negative enthalpy high manganese stainless steel material according to any one of claims 1-3, characterized in that, In the aforementioned negative enthalpy high-manganese stainless steel material Iron and manganese have negative enthalpies of mixing with aluminum, silicon, and carbon, respectively. ΔH mix (Fe-Al) = -11 kJ / mol,ΔH mix (Fe-Si) = -35 kJ / mol,ΔH mix (Fe-C) = -50 kJ / mol,ΔH mix (Mn-Al) = -19 kJ / mol,ΔH mix (Mn-Si) = -45 kJ / mol,ΔH mix (Mn-C) = -66 kJ / mol; The enthalpy of molybdenum mixed with iron and chromium are as follows: ΔHmix(Fe-Mo) = -2 kJ / mol, ΔHmix(Cr-Mo) = 0 kJ / mol.

5. The high corrosion-resistant negative enthalpy high manganese stainless steel material according to any one of claims 1-3, characterized in that, The negative enthalpy high-manganese stainless steel material is Fe 64 Mn 13 Al 13 Cr2Mo 1.5 Si 2.5 C4, Fe 50 Mn 20 Al 10 Cr 12 Mo1Si5C2, Fe 65 Mn 10 Al 10 Cr6Mo 1.5 Si 3.5 C4, Fe 59 Mn 15 Al 14 Cr 5.5 Mo 0.5 Si1C5 and Fe 56 Mn 18 Al 11 One of Cr8Mo1Si2C4.

6. A method for preparing a high corrosion-resistant negative enthalpy high-manganese stainless steel material according to any one of claims 1-5, characterized in that, The negative enthalpy high-manganese stainless steel material is Fe a Mn b Al c Cr d Mo e Si f C g ; in: a, b, c, d, e, f, and g correspond to the molar percentages of each element, 10%≤b≤20%, 10%≤c≤15%, 2%≤d≤12%, 0<e≤2%, 0<f≤5%, 2%≤g≤5%, with the balance being Fe and unavoidable impurities; The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps: According to the composition and molar percentage of the negative enthalpy high manganese stainless steel material, calculate and weigh each metal raw material, and put each metal raw material into a water-cooled metal crucible in order of melting point from low to high. The metal raw material with the lowest melting point is placed at the bottom, and the metal raw material with the highest melting point is placed on the surface. Sponge titanium is placed in the middle copper mold. Arc melting is carried out in an oxygen-free environment until it is fully mixed to obtain the negative enthalpy high manganese stainless steel material.

7. The method for preparing the high corrosion-resistant negative enthalpy high manganese stainless steel material according to claim 6, characterized in that, The oxygen-free environment is achieved through a process of vacuuming, argon filling, melting titanium sponge to absorb oxygen, and then vacuuming again.

8. The method for preparing the high corrosion-resistant negative enthalpy high manganese stainless steel material according to claim 7, characterized in that, The process of vacuuming, argon filling, melting titanium sponge and absorbing oxygen, and then vacuuming again is as follows: A mechanical pump was used to evacuate the vacuum to a level less than 5 Pa, followed by a molecular pump to evacuate the vacuum to 4*10 Pa. -4 - 7*10 -4 Pa, then 99.99% pure argon gas is introduced to 0.04-0.05 MPa, followed by arc ignition and melting of sponge titanium twice to absorb residual oxygen. Finally, a mechanical pump is used to evacuate to a vacuum level of less than 5 Pa, and a molecular pump is used to evacuate to 4*10 Pa. -4 - 7*10 -4 Pa.

9. The method for preparing the high corrosion-resistant negative enthalpy high manganese stainless steel material according to claim 6, characterized in that, The number of times the metal raw material is ignited and melted is greater than 4. After each ignition and melting, the alloy in the crucible is turned over before the next ignition and melting is carried out. The melting time for each arc-ignition melting is 1.0-2.0 min, and in addition to the first and last arc-ignition melting, the arc-ignition melting of the metal raw materials also includes magnetic stirring of the melt.

10. The method for preparing the high corrosion-resistant negative enthalpy high manganese stainless steel material according to any one of claims 6-9, characterized in that, The melting voltage and melting current for the arc-ignition melting are 10-15V and 200-300A, respectively.